Hubungan Status Gizi, Kebiasaan Mencuci Tangan Dan Pengelolaan Sampah Dengan Kejadian Diare Pada Balita Usia 24-59 Bulan Di RSUD Pagelaran Kabupaten Cianjur : (Relationship Between Nutritional Status, Hand Washing Habits, and Waste Management with the Incidence of Diarrhea in Toddlers Aged 24-59 Months at Pagelaran Hospital, Cianjur Regency - Arthaloka, Arthi Meilani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Diarrhea occurs worldwide and causes 4% of all deaths and 5% of health loss resulting in disability. Diarrhea remains the leading cause of death in children under 5 years of age in Sub-Saharan Africa. The risk factors for acute diarrhea vary by context and have important implications for reducing the burden of disease. Knowing the relationship between nutritional status, handwashing habits, and waste management with the incidence of diarrhea in toddlers aged 24-59 months at Pagelaran Hospital, Cianjur Regency in 2022. Methods: The research design used quantitative research with a cross-sectional design. The sample of this study was 90 toddlers aged 24-59 months. Results: Most of the respondents experienced abnormal nutritional status as many as 53 people (58.9%), Most of them had the habit of washing their hands properly as many as 58 people (64,4%); and most of the respondents had a good category of waste management as many as 52 people (57,8%); Most of the respondents experienced the incidence of diarrhea was 46 people (51,1%). There was a relationship between nutritional status, hand-washing habits, and waste management with the incidence of diarrhea. Discussion: The expected that this research can provide input, evaluation, and considerations related to Nutritional Status, Handwashing Habits, and Waste Management with Diarrhea.